Shear Behaviour of UHPC Concrete Beams. (2016) - Zagon, Raul; Zoltan, Kiss
Abstract: The work presented in this article aims to compare the experimental results on shear capacity of SFR-UHPC (steel fibre-reinforced ultra-high performance concrete) I-shaped beams against the modelling results. Steel fibres added to the concrete replace stirrups. The purpose of the paper is to confirm the feasibility of SFR-UHPC for I-shaped reinforced concrete beams and replacing classical stirrups by fibre reinforced concrete.